Correlating Reaction Dynamics and Size Change during the Photomechanical Transformation of 9‐Methylanthracene Single Crystals. (25th November 2021) - Morimoto, Kohei; Kitagawa, Daichi; Tong, Fei; Chalek, Kevin; Mueller, Leonard J.; Bardeen, Christopher J.; Kobatake, Seiya
Abstract: Photomechanical molecular crystals that expand under illumination could potentially be used as photon‐powered actuators. In this study, we find that the use of high‐quality single crystals of 9‐methylanthracene (9MA ) leads to more homogeneous reaction kinetics than that previously seen for polycrystalline samples, presumably due to a lower concentration of defects. Furthermore, simultaneous observation of absorbance and shape changes in single crystals revealed that the dimensional change mirrors the reaction progress, resulting in a smooth expansion of 7 % along the c ‐axis that is linearly correlated with reaction progress. The same expansion dynamics are highly reproducible across different single crystal samples. Organic single crystals exhibit well‐defined linear expansions during 100 % photoconversion, suggesting that this class of solid‐state phase change material could be used for actuation. Abstract : The development of a nonlinear kinetic model for crystal reactions allows us to quantify for the first time how the kinetics depend on sample morphology. Furthermore, the quantitative connection between molecular reaction kinetics and mechanical response in well‐defined single crystals provides a new benchmark for analyzing these photomechanical materials.